Mathematical Optimization Strategies for address Production Mixing Challenges - Ahmed, Hiba A.; Alridha, Ahmed Hasan (Iraqi Journal of Science, 2025)
The mixing problem is one of the most important problem in optimization strategies that falls within a wide range of applications, especially productivity ones, which makes it face many challenges. The problem is to determine how much of each item should be obtained and mixed with others so that the properties of the mixture fall within specified parameters and the total cost is minimized and the total profit is maximized. In this paper, we presented the problem modelling according to the linear optimization technique to obtain optimal results, which was implemented using the Python Pulp library. The proposed approach shows its effectiveness through advanced computational analysis in achieving compliance with the specified standards and obtaining maximum profit margins.